In Vitro Acaricidal Activity of Selected Medicinal Plants Traditionally Used against Ticks in Eastern Ethiopia - Jelalu Kemal; Tesfaheywet Zerihun; Sisay Alemu; Kedir Sali; Musa Nasir; Ashebr Abraha; Teka Feyera (Journal of Parasitology Research)
A study was carried out to evaluate the acaricidal activities of crude methanolic extract of leaves of six medicinal plants, namely, Vernonia amygdalina, Calpurnia aurea, Schinus molle, Ricinus communis, Croton macrostachyus, and Nicotiana tabacum, against Rhipicephalus (Boophilus) decoloratus and Rhipicephalus pulchellus using an in vitro adult immersion test. Five graded concentrations of the crude extracts, 6.25, 12.5, 25, 50, and 100 mg/ml, were tested at different time intervals, and temporal changes in tick viability were recorded for 24 hours. Diazinon (0.1%) and distilled water were used as positive and negative controls, respectively. Standard procedures were applied to screen the phytochemical constituents of the tested plant parts. Phytochemical screening showed the presence of a condensed amount of tannins in all extracts. Starting from 30 min post exposure, the 100 mg/ml concentration of C. aurea and R. communis extracts has caused significantly higher mortality (P<0.05) compared to the diazinon. A significant increase in tick mortality started 2 hr post exposure with diazinon and 50 and 100 mg/ml concentrations of S. molle. Vernonia amygdalina extract and diazinon showed a significant increase in tick mortality 3 hr post exposure with 100 mg/ml concentration. Similarly, a significant increase in tick mortality started 2 hr post exposure with diazinon and 100 mg/ml concentrations of C. macrostachyus and N. tabacum. At 24 hr post exposure, diazinon and 50 and 100 mg/ml concentrations of all the extracts have caused significantly higher tick mortality than the rest of the concentrations (P<0.05). Higher concentrations of all the extracts had showed a comparable and strong acaricidal effect on Rhipicephalus (Boophilus) decoloratus and Rhipicephalus pulchellus having no significant difference with that of the positive control (P>0.05) at 24 hr post exposure period. Tick killing activity of all evaluated plant extracts increases with increasing exposure time and concentration as well. Thus, all the tested plants could be used against Rhipicephalus (Boophilus) decoloratus and Rhipicephalus pulchellus as a potential alternative to substitute commercially available drugs. We recommend further study on fractionating each component separately and validating the materials.